The influence of T-Shape flow deflector placement on convection heat transfer over an array heated blocks - Hamza, AMIRAT (2025)
In this research, a numerical study was conducted to examine the convective heat transfer in a horizontal channel containing multiple heated blocks. The channel design incorporates T-shaped flow deflectors strategically positioned downstream of each block. Air, with a Prandtl number of 0.71 and consistent thermal properties, is used for cooling. The geometric attributes and arrangement of the flow deflectors remain consistent throughout the analysis. The computations are based on a Reynolds number of 400, with systematic variations in the positions of the flow deflectors. The finite volume method, implemented using Ansys Fluent© software, is employed to solve the governing mathematical equations numerically. The results emphasize the significant impact of adjustments to the flow deflector configuration on both fluid flow patterns and heat transfer characteristics across the heated blocks.